MODE OF DELIVERY DOES NOT CORRELATE FETAL OUTCOME IN PREGNANCY WITH COVID-19 AT DR. M. DJAMIL HOSPITAL PADANG - Farnas, Heri; Sriyanti, Roza (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction: Corona Virus Disease 2019 (COVID-19) was first reported in Wuhan, China. Knowledge about COVID-19 infection in relation to pregnancy and the fetus is still limited. Report from China shows high rate of caesarean delivery (> 90%) due to the suspicion for vertical transmission. Globally there is an increase of caesarean delivery in women with COVID-19 infection. Clinical implications mode of delivery in pregnancies with COVID-19 infection are not fully understood.Objective: The aims of this study to assess differences in fetal outcome based on the mode of delivery in pregnancies with COVID-19 infection.Methods: This observational analytic study with cross sectional study design was conducted in single center at dr. M. Djamil General Hospital Padang from March 2020-March 2021. All study subjects qualified to inclusion and exclusion criteria included. The fetal outcome analyzed based on APGAR scores and COVID-19 status in newborn baby using Mann-Whitney test.Results: A total of 49 patients were analyzed. The results showed mean APGAR score 1 minute in the vaginal delivery was lower than caesarean delivery (6.87±1.06 vs 7.38±0.82) but not significant (p=0.09). No significant difference between vaginal delivery and caesarean delivery based on APGAR score 5 minutes (p=0.19). None newborn babies infected with COVID-19 in both groups.Conclusions: There was no difference of fetal outcome based on the APGAR score in pregnancies with COVID-19 infection by mode of delivery. There were no cases of infants with COVID-19 infection in both groups.Keywords: COVID-19, mode of delivery, APGAR score